2011
DOI: 10.1007/s12064-011-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Information processing in echo state networks at the edge of chaos

Abstract: We investigate information processing in randomly connected recurrent neural networks. It has been shown previously that the computational capabilities of these networks are maximized when the recurrent layer is close to the border between a stable and an unstable dynamics regime, the so called edge of chaos. The reasons, however, for this maximized performance are not completely understood. We adopt an information-theoretical framework and are for the first time able to quantify the computational capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
241
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(258 citation statements)
references
References 35 publications
13
241
4
Order By: Relevance
“…(Indeed, as noted earlier, SIS dynamics have been used to model dynamics on brain networks [38]). Our results in this paper regarding SIS dynamics continue to add to the quantitative evidence regarding the maximisation of information storage and transfer as intrinsic computational properties at or near critical states, as previously found in a diverse range of dynamics and network structures including the Ising model [25], recurrent neural networks [26], gene regulatory network (GRN) models [23], and regular-small-world-random transitions in structure [24]. In this way, we have provided another important link for epidemic spreading models to complex networks, criticality and information dynamics.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(Indeed, as noted earlier, SIS dynamics have been used to model dynamics on brain networks [38]). Our results in this paper regarding SIS dynamics continue to add to the quantitative evidence regarding the maximisation of information storage and transfer as intrinsic computational properties at or near critical states, as previously found in a diverse range of dynamics and network structures including the Ising model [25], recurrent neural networks [26], gene regulatory network (GRN) models [23], and regular-small-world-random transitions in structure [24]. In this way, we have provided another important link for epidemic spreading models to complex networks, criticality and information dynamics.…”
Section: Discussionsupporting
confidence: 80%
“…This is particularly the case in complex systems and network approaches to computational neuroscience, where it is conjectured that the brain is in or near a critical state so as to advantageously use maximised computational properties here [26,[45][46][47][48]. (Indeed, as noted earlier, SIS dynamics have been used to model dynamics on brain networks [38]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can try |λ| max = 1 and see if this improves the network performance and how this impacts the memory of the reservoir on earlier events. Steps toward this direction have been made by going near the "edge of chaos" [5] or even further where the network may not be an echo state network for all possible input sequences but instead just around some permissible inputs [6]. Presumably, these approaches still all forget exponentially fast.…”
Section: For Esns)mentioning
confidence: 99%
“…Although a random recurrent connectivity pattern can be used, heuristically it has been found that typically the performance of the network depends strongly on the statistical features of this random connectivity (cf. for example [5] …”
Section: Introductionmentioning
confidence: 99%